2006
DOI: 10.1515/cclm.2006.079
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and their inhibitors in different acute stroke subtypes

Abstract: The aim of the study was to determine serum levels of selected matrix metalloproteinases (MMPs) and their natural inhibitors (TIMPs) in the acute phase of different stroke types subdivided according to the Oxfordshire Community Stroke Project (OCSP) classification and the possibility of discriminating stroke types according to their levels. The study included 126 patients with acute stroke within the first 24 h of symptom onset, and 124 healthy volunteers. The stroke group had lower MMP-2 concentrations and MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…The observed low levels of MMP-2 in our study are consistent with other data finding reduced MMP-2 concentrations during the acute phase of stroke compared to controls [48, 49]. In contrast, Chang et al [50 ]demonstrated the coordinate expression of the direct and indirect MMP-2 activators immediately after experimental middle cerebral artery occlusion.…”
Section: Discussionsupporting
confidence: 92%
“…The observed low levels of MMP-2 in our study are consistent with other data finding reduced MMP-2 concentrations during the acute phase of stroke compared to controls [48, 49]. In contrast, Chang et al [50 ]demonstrated the coordinate expression of the direct and indirect MMP-2 activators immediately after experimental middle cerebral artery occlusion.…”
Section: Discussionsupporting
confidence: 92%
“…Three months later the TIMP-2 serum levels went back to normal. In contrast to the results of Horstmann and Alvarez-Sabin, Vukasovic et al [23] noted an increase in TIMP-2 levels following stroke (Croatia, n = 250). Rosenberg et al [24] created an experimental stroke model with rats and measured increasing TIMP-2 levels over 14 days with maximum levels on day 5.…”
Section: Discussionmentioning
confidence: 56%
“…Acute MMP-9 concentrations have also been related to infarct size, poor neurological outcome, and hemorrhagic transformation complications (63,65,66 ). MMP-9 concentrations assessed at hospital admission have been identified as a predictor of infarct volume as measured with diffusion-weighted MRI (67 ), and the biomarker is further correlated with stroke lesion growth, even with the effective application of thrombolytic therapy (68 ).…”
Section: Matrix Metalloproteinmentioning
confidence: 99%